Nurture corners in preschool settings: involving and nurturing children and parents. Issue 4 (2nd October 2017) - Stone, Kelly; Burgess, Cheryl; Daniel, Brigid; Smith, Joanna; Stephen, Christine
ABSTRACT: This article draws on the findings from a small qualitative study which focused on gathering perspectives and accounts of experiences from nursery practitioners, health and third sector professionals and parents. It explored the ways in which parents/carers and practitioners experienced the nurture approach developed in preschool settings in Glasgow, Scotland and their perspectives on the impact that this provision has had on the development and well-being of young children and family engagement in learning.  The findings provided some insights into the specific ways in which settings involved parents and worked towards developing a nurturing ethos towards parents themselves, underpinned by the following three elements: a welcoming setting, sensitive and empathic staff and creative practice. The particular characteristics of these three elements seemed to support some parents in developing the parenting skills which were required to consolidate the benefits experienced by their children. These benefits included parents being supported to replicate some of the practices at home and becoming more involved in their children's learning. The study identified challenges for some nurseries in achieving this, such as the limited scope for nurture corner practitioners in some of the settings to fully utilise their skills with parents due to accommodation constraints.